Writers, Literature and Censorship in Poland. 1948?1958 - Nycz, Ryszard; Nycz, Ryszard; Budrowska, Kamila (Peter Lang, 2019)
The book describes the system of communist censorship in Poland in the years 1948?1958, as well as its effects on the development of literature. It is the first literary studies work which takes up the subject in such broad and systematic terms. The book is divided into three main parts: an attempt at synthesis (theory and practice of censorship), special cases (censorship of specific writers), authorial strategies (the authors' ways of dealing with censorship) and contexts. The most important conclusion which can be drawn from the research is that out of many small changes emerges an image of a very significant one. Numerous small cuts and alterations build up to an image of Polish literature of the 1940s and 1950s as a whole. A whole that was always dependant on and subservient to politics.